One simple method to mitigate the structure degradation of alloy catalyst layer in PEMFC. (10th November 2019) - Li, Wenbin; Lin, Rui; Yang, Yue
Abstract: There are two ways to solve the durability problem of catalyst layer made by alloy catalyst, taking PtNi/C for example, in proton exchange membrane fuel cell: (1) using alloy catalyst with special structure to inhibit the dissolution of Ni; (2) designing special catalyst layer structure to reduce its sensitivity to Ni contamination. This article mainly focuses on way (2). A special catalyst layer structure with dual layer is proposed and Pt1 Ni1 /C catalyst is used to verify the structure. The aim is to use a simple design that is close to commercialized production to mitigate catalyst layer degradation caused by Ni contamination. Accelerated stress test has been conducted to compare the durability of catalyst layer with different structures (single layer made by PtNi/C and dual layer). Polarization curves, electrochemical impedance spectroscopy curves and cyclic voltammetry curves at specific current have been recorded during the AST.